EXTENDED REALITY APPLICATIONS IN BUSINESS COMMUNICATION AND DEVELOPMENT: UNVEILING FUTURE HORIZONS - Jerly. J; P. Sathya (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Extended Reality (XR) is an interactive communication technology. It helps in providing a physical representation of a virtual environment or things that the user can interact with, within the real-world scenario. Extended Reality is an umbrella term which encompasses Virtual Reality (VR), Augmented Reality (AR), and Mixed Reality (MR). The applications of XR helps the user to place virtual objects in the physical world to look for its suitability and opens doors for immersive interactions with the placed objects. It gives the user a sense of being a part of the digital world and immersive try-on experiences. In the context of business, integration of XR has completely changed various fields like customer engagement, product design, marketing, Global connection, and communication, etc. Through XR, it became easy for the business sectors to train their employees without risking cost or lives. Overall, XR as a cutting-edge technology has a great potential to bring enormous development in the field of business. In this paper, the researcher highlights the importance of implementing XR in business firms. Specifically, this paper emphasizes its role in business communication and commercials. It sheds light on the various benefits of using Extended Reality for the enhancement of businesses.